PENGGUNAAN PERMAINAN UNO CARD SEBAGAI MEDIA CHEMO-EDUTAINMENT UNTUK MENINGKATKAN AKTIVITAS DAN KETUNTASAN BELAJAR SISWA PADA MATERI SISTEM PERIODIK UNSUR DI KELAS X.10 SMA NEGERI 2 TAMBANG - Lani Marlisa; Jimmi Copriady; Maria Erna (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This study aims to improve the activity and mastery learning students on the material elements of class X.10 Senior High School of class X.10. This form of research is the Research Action Class . The study was conducted collaboratively, where researchers and teachers cooperate at this stage of planning, implementation, observation, and reflection. The implementation of the actions carried out by teachers, while a researcher as an observer. The research subject is class X.10 SMA Negeri 2 Tambang year 2016/2017 which amounted to 37 students, consisting of 17 male students and 20 female students. The research results obtained are the use of Uno Card games as the Chemo-Edutinment media can improve the learning activities of students of class X.10 SMA Negeri 2 Tambang with the percentage average cycle I of 70,57% and 85,89% for the second cycle. The use of Uno Card games as the Chemo-Edutainment media can improve learning completeness students in class X.10 of SMA Negeri 2 Tambang with the percentage amounted to 91,90% the first cycle and the second cycle of 100%.